Evaluation of surface treatments on 5052-H32 aluminum alloy for enhancing the interfacial adhesion of thermoplastic-based fiber metal laminates. (April 2018) - Gonzalez-Canche, N.G.; Flores-Johnson, E.A.; Cortes, P.; Carrillo, J.G.
Abstract: The interfacial polymer-metal adhesive property in layered materials such as fiber metal laminates (FMLs) is an important factor in their mechanical performance due to the stress transfer between the metal layers and the fiber-reinforced composite material. This study evaluates the effect of surface treatments applied to an aluminum alloy Al5052-H32 used as the metal skin layer of a FML based on aramid fiber reinforced polypropylene. Here, wettability, morphology and chemical analyses were performed on the metal alloy to characterize the surface treatments via contact angle, scanning electron microscopy (SEM), profilometry, and x-ray photoelectron spectroscopy (XPS). The degree of adhesion between the aluminum layers and the composite material was evaluated via shear adhesion strength testing, whilst the mechanical performance of FML was evaluated through uniaxial tensile testing. The results showed that the treatment of the metal layers by a sodium hydroxide and nitric acid pickling process increases the degree of adhesion and tensile strength of the FML arrangements here investigated.